PENGARUH RETRIBUSI DAERAH, PAJAK DAERAH DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI BALI - Pramartha, Agung; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
ABSTRACT The contribution of local taxes and taxes that have been established with the legislation is very helpful to the local revenue for the local government in reducing the burden of the central government. If local revenue increases, regional development will be more optimal. Levies and taxes managed by the region, as well as by the provincial government of Bali. So the researchers feel interested to examine the effect of regional levies, local taxes and the number of residents simultaneously also partially to the original income area of ??Bali Province.Based on the data results, it is known that the regression model successfully pass the classical assumption test. From the results of the test f explains that the variable of regional levy, local taxes and the number of residents have a positive and significant impact on local revenue (PAD). Whereas in t test it is explained that only partial taxes are partially derived indigenous revenue. Local retribution and partial population are not positively and positively influenced by local income. Keywords : Local Levies, Local Taxes, Population, Local Revenue